Тенденции и перспективы социально-экономического развития Республики Крым в результате институциональной трансформации - Боровская, Л.В. (Культура народов Причерноморья, 2014)
В статье рассмотрены проблемы социально-экономического развития Республики Крым на современном этапе, дна качественная и количественная оценка, обосновано принятие программы развития Республики Крым в условиях трансформации. У статті розглянуто проблеми соціально-економічного розвитку Республіки Крим на сучасному етапі, надана якісна і кількісна оцінка, обгрунтовано прийняття програми розвитку Республіки Крим в умовах трансформації. The article deals with the problems of socio-economic development of the Republic of Crimea at the present stage, revealed a negative trend decrease in virtually all sectors of industry, construction, agriculture, due to the rupture of economic ties with Ukraine and unstable foreign policy situation. All this necessitates the development of a program development Republic of Crimea and Sevastopol, which would correspond to the requirements of institutional restructuring, reorientation and integration of the Russian economy. Determined that it is currently necessary to the implementation of comprehensive programs of modernization of fixed assets on the basis of energy efficiency, resource efficiency. Development of the Republic of Crimea in the medium term will be constrained by the transport factor. A qualitative and quantitative assessment, justified the adoption of the program of development of RC in the transformation.